The Effectiveness of Logotherapy on Depression and Positive Psychological Characteristics of the Elderly - Arghavan Shariat (Razi University, 2021)
The elderly age seems to be a proper time for finding the meaning of life and personal growth compared to other periods of life. The existence of meaning in life of the elderly is an important factor for the continuation of their life and finding meaning in life serve an important role in mental health and quality of life of the elderly. Therefore, this research aimed to investigate the effectiveness of logotherapy on depression and positive psychological characteristics of the elderly living in Isfahan. The research method was semi-experimental with pretest-posttest and follow-up design with a control group. The participants included all the elderly aged above 60 years old living in Isfahan. First, two centers were selected among Retired Teachers Associations and then, 40 participants were selected purposefully based on inclusion and exclusion criteria and were randomly assigned with an equal ratio into the experimental and control groups (20 participants each). The experiment group were exposed to the Logotherapy for 11 90-minute sessions, while control group did not receive any intervention at this time. Measurs consisted of Yasavage et. al’s elderly depression scale and Rashid’s positive psychological characteristics scale. Utilized to analyze of the data was SPSS-23 software. Analysis of Covariance (ANCOVA) demonstrated that logotherapy has a significant role in improving depression and positive psychological characteristics of the elderly (P<0.05). According to the findings of the current research, logotherapy can be used as an efficient method at counselling and psychotherapy centers in order to creat good feeling in the elderly, in turn leading to the decrease of their inanity feeling and depression.ReferencesAhmarian, F., Khodabakhsi Koolaee, A., Falsafinejad, M. (2015). The Effects' of group logo-therapy on life expectancy and sleep quality in elderlies of boarding center of Tehran city. Journal of Research Beligion & Health, 1 (3), 11-18. [Persian]Amani, R. (2015). The Effectiveness of structured group reminiscence on the enhancement of elderl’s positive self- concept. Journal of Aging Psychology, 1(1), 1-9. [Persian]Ansari, M., Doulatshahi, B & Sahaf, R. (2019). Comparing negative emotional components in older people with normal and poor quality of sleep. Iranian Journal of Ageing (Salmand), 14(2), 200-211. [Persian]Asghari, N., Ali Akbari M., & Dadkhah A. (2012). The effects of group logotherapy on decreasing the degree of depression in female olds. Middle Eastern Journal of Disablitity Studies, 2(1), 31- 38.Azadi, A., Taghinezhad, H., Bastami, M., Bastami, AR., & Pashaei sabet. (2016). The study amount of anxiety and depression among elderly diabetic patients referred to Shahid Mostafa Khomeini in Ilam and shohada Ashayer Hospitals in khoramabad 2015. Iranian Journal of Narsing Research.3 (11), 1-9. [Persian]Bagheri, H., Sadeghi, M., Esmaeili, N & Naeimi, Z. (2016). Relationship between spiritual health and depression and quality of sleep in the older adults in Shahroud. Journal of Gerontology (joge), 1(1), 55-62. [Persian]Banisi, P. (2019). The Effectiveness of positivism training on subject well- being positive meta-emotion and self- management ability in the elderly women. Journal of Aging Psychology, 5 (3), 217- 227. [Persian]Banisi, P. (2018). The Effectiveness of stress management training on psychological health, self- efficacy and happiness in elderly women with moderate depression. Aging Psychology, 6(1), 53-64.[Persian]Bettio, L. E., Rajendran, L., & Gil-Mohapel, J. (2017). The effects of aging in the hippocampus and cognitive decline. Neuroscience & Biobehavioral Reviews, 79, 66-86.Brise, N., C, Camp., & Snclgar, R. (2012). Psychology data analysis by the application of spss. (A. Samadi & kh. Aliabadi, Trans.). Davarn Publication. (Original Language release date, 2006) [Persian]Choobforoush, A., Mohammad Panah Ardakan, A., Behjati Ardakan, F & Ahmadi Ardakani, Z. (2018). Effectireness of life review therapy on depression rate and life satisfaction of elderly. Journal of Aging Psychology, 4(2), 155-164. [Persian]Fakhar, F., Navayinezhad, S., & Foroughan, M. (2008). The Role of group counseling with logo-therapeutic approach on the mental health of older women. Iranian Journal of Ageing (Salmand), 3 (1), 58-[Persian]Fancourt, D., & Tymoszuk, U. (2019). Cultural engagement and incident depression in older adults: evidence from the English Longitudinal Study of Ageing. The British Journal of Psychiatry, 214(4), 225-229.Farnam, A. (2016). The Effect of positive thinking in enhancement of quality and hope of life among the elderly. Positive Psychology Research, 2 (1), 75- 88. [Persian]Farokhzadian, A & Mirderekvand, F. (2018). The Effectiveness of self- compassion focused therapy on increase of psychological well- being and reduction of depression in the elderly. Journal of Aging Psychology, 13(4), 293- 302. [Persian]Fleiss, J. L., Levin, B., & Paik, M. C. (1981). The analysis of data from matched samples. statistical methods for rates and proportions. Third Edition, 373-406.Frankl, V. (2019). The doctor and the soul. (F Seif Behzad Trans.) Dorsa, 5, 4-360. [Persian]Frankl, V. (2021). The will to meaning: Foundations and applications of Logotherapy. (M Milani, Trans.) Dorsa, 6, 5-208. [Persian]Frouzande, Z., Mami, Sh & Amani, O. (2020). The Effectiveness of group logotherapy on resiliency, depression and quality of life in elderly. Journal of Gerontology (joge), 4(4), 19-29. [Persian]Ghadampour, E., Moradizadeh, S & Shahkarami, M. (2018). The Effectiveness of mindfalness training on increasing happiness and improve quality of life in elderly. Journal of Aging Psychology, 4(1), 27-38. [Persian]Ghasemi Pirbalouti, M., Shariat, A., & Ghazanfari, A. (2019). A Meta-Analysis of exercise therapy on reducing depression among older adults in Iran. Quarerly Journal of Health Psychology, 8(30), 69- 80. [Persian]Ghorbani, Z., Banijamali, Sh., Ameri, F., Khosravi, Z & Dehshiri, Gh. (2015). Investigating psychometric properties of the persian version of positive psychotherapy inventory. Positive Psychology Research, 2(2), 15-26. [Persian]Golestanifar, S & Dasht Bozorgi, Z. (2020). The Effectiveness of acceptance and commitment based therapy on depression, psycholigical health and life expectancy in the elderly with nonclinical depression. Aging Psyhchology, 6(3), 191-203. [Persian]Habibi Sola, A., Nikpour, S., Sohbatzadeh, R., Haghani, H., (2008). Quality of life in elderly people of west of Tehran. Nursing Research. 2(7), 29- 35. [Persion]Ho, H.C., Yeung, D.Y., & Kwok, S.Y. (2014). Development and evaluation of the positive psychology intervention for older adults. The Journal of Positive Psychology, 9(3), 187- 197.Hojiazizi, A., Bahmani, B., Mahdi, N., Manzari Tavakoli, V., & Barshan, A. (2017). Effectiveness of group effectiveness of group logotherapy on death anxiety and life expectancy of the elderly living in boarding houses in Kerman. Iranian Jouranl of Ageing, 2(12), 222-230. [Persian]Holsti, L.R. (2019). Content analysis of humanity and social sciences. (N. Salarzadeh Amiri, Trans.) Alame Tabatabaee University Publication.Hutchinson, G.T., & Chapman man, B.P. (2005). Logotherapy-enhanced REBT: An integration of discovery and reason. Journal of contemporary psychotherapy, 35(2), 145- 155.Jabarouti, R., Shariat, A., & Shariat, A. (2014). Effect of persian classic poetry on the level of stress hormone in retired academicians. Journal of Poetry Therapy, 27(1), 25-33.Javanmardi, F., Naeimi, E & Moatamedy, A. (2020). The Effectiveness of mindfulness model on improving intimate attitudes model on improving intimate attitudes and elderly depression. Aging Psychology, 6(1), 39-52. [Persion]Kang, K. A., Im, J. I., Kim, H. S., Kim, S. J., Song, M. K., & Sim, S. Y. (2009). The Effect of logotherapy on the suffering, finding meaning, and suffering, well-being of adolescents with Terminal Cancer. Child Health Nursing Research, 15(2), 136-144.Khaledian, M., Sohrabi, F. (2015). Effectiveness of group logotherapy on reducing depression and increasing hope in elderly with empty Nest Syndrome. Clinical Psychology Studies, 15(4), 79-104. [Persian]Khezri Moghadam, N., Vahidi, S & Ashormahani, M. (2018). Efficiency of cognitive –existentaial group therapy on life expectancy and depression of elderly residing in nursing homes. Iranian Journal of Ageing, 13(1), 62-73. [Persian]Kim, S., & Park, K.S. (2016). A Meta-Analysis on variables related to death anxiety of elderly in Korea. Korean Journal of Adult Nursing, 28(2), 156-168.Komp, K., & Aartsen, M. (2013). Old age in Europe. A Textbook of gerontology. Dortrecht: Springer Netherland.Koohpayezadeh, F., Motamedi, A., Dortaj, F., Eskandari, H & Farrokhi, N. (2019). Effectiveness of a psychological- educational package based on the logo therapy on loneliness and self- efficacy of retired teachers. Journal of Gerontology (joge), 4(1), 24- 33. [Persian]Lee HCB, Chiu HFK, Kwok WY. et al. (1993). Chinese elderly and the GDS short form: A preliminary study. Clinical Gerontologist: The journal of Aging and Mental Health,14(2), 37-42.Majzoobi, M. R., Momeni, Kh., Amani, R., & Hojjat Khah, M. (2012). The Effectiveness of structured group reminiscence on the enhancement of the elderlyes life quality and happiness. Developmental psychology: Iranian Psychologists, 9(4), 189- 2020. [Persian]Malakouti, K., Fathollahi, P., Mirabzadeh, A., Salavati, M., & Kahani, S. (2006). Validation of geriatric depression scale (GDS-15) in Iran. Research in Medicine, 30(4). 361-369. [Persian].Mohammad, L & Gholami Heidarabadi. (2019). The Effective of training the problem solving –based cognitive strategies on depression in elderly women. Journal of Aging Psychology, 4(4), 337- 349. [Persian]Morgan, J.H. (2013). Late- life depression and the counseling agenda: exploring geriatric logotherapy as a treatment modality. International Journal of Psychological Research, 6(1), 94-101.Motamedi, A. (2019). Psychology of aging. The Organization for Researching and Composing University Textbooks in the Humanities (SAMT).Motamedi, A., Mostafapour, V., & Farokhi, H. (2018). The Effectiveness of hope group therapy on enhancement of happiness and quality of life in elderly women in tasouj. Iraninan of Aging Psychology, 3(4), 243- 252. [Persian]Mui AC. (1996). Geriatric depression scale as a community screening instrument for elderly Chinese immigrants. International Psychogeriatrics, 8(3), 445-458.Ohayon MM., Carskadon, MA., & Guilleminault, C., Vitiello, MV. (2004). Meta-analysis of quantitative sleep parameters from childhood to old age in healthy individuals: developing normative sleep values across the huam lifespan. Sleep-newYork then Westchester, 24, 74- 1255.Orang, S., Hashemi Kazini, H & Ramshini, M. (2018). Investigating the meaning of life and psychological well-being, in youth, adults, and elderly (A Comparative study of three age graps). Iranian Journal of Ageing, 13(2), 182-197. [Persian]Ouweneel, E., Schaufeli, W.B., & Le Blanc, P.M. (2013). Believe, and you will achieve: Changes over time in self- efficacy, engagement, and performance. Applied Psychology: Health and Well-Being, 5(2), 225-247.Park, N., Peterson, C., Seligman, MEP. (2004). Strengths of character and well-being. Journal of Social and Clinical Psychology, 23(5), 19- 306.Parpaee, R & Kakaberaei, K. (2018). The Effectiveness of logotherapy on decreasing depression and anxiety in the elderly women with Empty Nest Syndrome. Journal of Aging Psychology, 4(1), 51- 59. [Persian]Parpaee, R., & Kakaberaei, K. (2018). The Effectiveness of logottherapy on decreasing depression and anxiety in the elderly women with empty nest syndrome. Aging Psychology, 4(1), 51-59. [Persian]Psarra, E., & Kleftaras, G. (2013). Daptation to physical disabilities: the role of meaning in life and depression. The European Journal of counselling psychology, 2(1), 79-99.Rafati, N., Yavari, P., Mehrabi, Y., Montazeri, A. (2005). A Quality of life among Kahrizak Charity Institutionalizd elderly People. Journal of School of Public Health and Institue of Public Health Research, 3(2), 65-75.  [Persian]Raivio, M., Kautiainen, H., Immonen, S., & Pitkälä, K. (2016). Alcohol use and happiness among retired finns living in Spain compared to those in Finaland. European Geriatric Medicine, 7(1), 3-7.Rajabi, F & Aslami, E. (2019). The effect of group life skills training on psychological well- being and happiness in elderly women members of the Jahandidegan city of Abadan city. Journal of Aging Psychology, 4(4), 301- 312. [Persian]Rashid, T. (2008). Positive psychotherapy. In S.J. Lopez (Ed). Positive psychology exploring the best in people. Westport, CT. Greenwood Publishing Company, 4, 187- 217.Rashid. T. (2015). Positive psychotherapy: A strength-based approach. The Journal of Positive Psychology, 10(1), 25- 40.Saeidimehr, S., Geravandi, S., Izadmehr, A & Mohammadi, M. (2016). Relationship between the “quality of life” and symptoms of depressior among older adults. Iranian Journal of Ageing, 11(1), 90-99. [Persian]Safari, S., & Akbari, B. (2018). Effectiveness of positive thinking training on psychological well-being and quality of life in the elderly. Avicenna Journal Neuro Psycho Physiology, 5(3), 113-122.Saffarinina, M., & Dortaj, A. (2018). Effect of group logotherapy on life expectancy and mental and social wellbeing of the female elderly residents of nursing homes in Dubai. Iranian Journal of Ageing, 12(4), 482- 493.Seligman, M.E. (2011). Flourish: a visionary new understanding of happiness and well-being. Policy. 27(3), 60-68.Shahandeh, M., & Abiyat, N. (2019). The effectiveness of hope therapy on islamic optimism and happiness of the elderly. Journal of Aging Psychology, 5(2), 117- 130. [Persian]Shamsaei, F., Cheraghi, F., Esmaeili, R., & Mohsenifard, J., (2014). Explanation of loneliness in the elderly and comparison with pscyhosoeial development theory: A Quantitative study. Journal of Education and Community Health, 1(2), 30- 38. [Persian]Shariat A., Gharmarani, A., & Abedi, A. (2014). Meta analysis of psychological intervention' effectiveness on the rate of depression among elerly Iranian in 2000-2010. SALMAND, 9 (1), 46- 53. [Persian]Shogaeyan, M., Sodani, & M., & Moradi, F. (2014). The Effectiveness of group logotherapy on the increase of life expectancy in retired men of the retirement center of mamasani. Armaghane-danesh, Yasuj University of Medical Seiences Journal (YUMSJ), 19 (6), 497- 506. [Persian]Sodani, M., Salehizadeh, A., & Mohammadi, K. (2015) Systematic Review of Therapeutic- Educational Protocolls In Counselling and Psychotherapy.  Avayenoor, 3, 11- 224. [Persian]Su, H., Cao, J., Zhou, Y., Wang, L., & Xing, L. (2018). The mediating effect of coping style on personality and mental health among elderly Chinese empty- nester: A cross-sectional study. Archives of gerontology and geriatrics. 75, 197-201.Taghvaeenia, A & Delavarizadeh, S. (2017). The Effectiveness of group logotherapy on the increase of psychological well- being of the elderly retired women. Journal of Aging Psychology, 2(2), 115-124. [Persian]Taghvaeenia, A., & Delavarizadeh, S. (2017). The Effectiveness of group logotherapy on the increase of psychological well- being of the elderly retired women. Journal of Aging Psychology, 2(2), 115-124. [Persian]Tehranizadeh, M., Shahbazi., F & Ahmadnia., A. (2019). The Effectiveness of Fornkl’s logotherapy in reducing depression among elderly in the districts of Tehran. The 4th International Confesence on Psychology and Educational Sciences, 1-8. [Persian]Word Health Organization. (2019). Global status report on alcohol and health 2018. Word Health Organization.Yazdanbakhsh., N., Younesi., J., Azimiyan, S & Foroughan, M. (2016). Ellects of group counseling based on logo therapy to decrease loneliness in elderly men. Iranian Journal of Ageing, 11(3), 392- 399. [Persian]Yazdkhasti, F. (2010). A Study on cognitive and depressive disorders in the elderly and their correlation with each other. Advances in Cognitive Science, 11 (4), 12- 77. [Persian]Yesavage, J. A., Brink, T. L., Rose, T. L., Lum, O., Huang, V., Adey, M., & Leirer, V. O. (1982). Development and validation of a geriatric depression screening scale: a preliminary report. Journal of psychiatric research, 17(1), 37-49.